Integrating phytochemical analysis and experimental validation of Ziziphus jujuba seed powder and oil to ameliorate CCl4-induced liver fibrosis in sprague dawley rats - Laiba Tanvir; Khurram Afzal; Asad Abbas; Adnan Amjad; Talha Bin Iqbal; Naeem Sarwar; Rameen Naeem; Ayman Furqan; Bipindra Pandey (PLoS ONE, 2026)
Liver fibrosis, a consequence of chronic liver injury, is characterized by excessive accumulation of the extracellular matrix, oxidative stress, and activation of hepatic stellate cells. This study evaluated the effectiveness of Ziziphus jujuba ( Z. jujuba ) seed powder and seed oil, both separately and in combination, in alleviating CCl 4 -induced liver fibrosis, and linked the in vivo effects to their phytochemical profiles. The seed powder extracts, using acetone and ethanol, showed significant antioxidant activity, with DPPH values reaching up to 90.13%, and exhibited a high phenolic content of 79.57 mg GAE/g in the ethanol extract. Gas chromatography–mass spectrometry (GC–MS) analysis identified several bioactive compounds, including derivatives of 1,4-benzenedicarboxylic acid (30.46% in powder, 20.43% in oil), hexanedioic acid bis(2-ethylhexyl) ester (25.31% in powder, 20.78% in oil), and oleic acid (10.61% in powder, 16.06% in oil. In vivo, carbon tetrachloride (CCl 4 ) administration led to elevated levels of ALT, AST, ALP, and bilirubin, causing disruptions in oxidative, lipid, inflammatory, hematological, and nutritional parameters. All treatment groups showed improvements in these parameters, with Group 4 (G 4 ) exhibiting the most pronounced hepatoprotective effects, including reductions in ALT (75.56 U/L), AST (125.76 U/L), ALP (125.43 U/L), and bilirubin (0.40 mg/dL) levels. Oxidative stress markers were reduced, with MDA at 5.47 nmol/g protein and NOx at 46.81 nmol/g protein, whereas antioxidant defenses were enhanced, as evidenced by SOD activity at 71.69 U/mg and catalase restoration. Lipid profiles were normalized, with triglycerides (TG) at 80.01 mg/dL, HDL at 34.60 mg/dL, and LDL at 22.30 mg/dL. Additionally, cytokine levels, specifically TNF-α and IL-6, decreased, red and white blood cell differentials were restored, and feed and water intakes and serum protein levels improved. These findings highlight the synergistic anti-fibrotic and hepatoprotective properties of Z. jujuba seed powder and oil, likely facilitated by the bioactive compounds in both the polar and lipid phases. However, further research into histopathology and confirmation of molecular pathways is crucial for clinical application.